2018
DOI: 10.1186/s12936-018-2190-z
|View full text |Cite
|
Sign up to set email alerts
|

Primaquine ineligibility in anti-relapse therapy of Plasmodium vivax malaria: the problem of G6PD deficiency and cytochrome P-450 2D6 polymorphisms

Abstract: The hypnozoite reservoir of Plasmodium vivax represents both the greatest obstacle and opportunity for ultimately eradicating this species. It is silent and cannot be diagnosed until it awakens and provokes a clinical attack with attendant morbidity, risk of mortality, and opportunities for onward transmission. The only licensed drug that kills hypnozoites is primaquine, which attacks the hypnozoite reservoir but imposes serious obstacles in doing so—at hypnozoitocidal doses, it invariably causes a threatening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 20 publications
2
97
0
Order By: Relevance
“…Its CDS is 1338~1491bp in length and encodes 446 497 amino acids. The heterogeneity of CYP2D6 monooxygenase activity varies from complete dysfunction to ultra-rapid enzyme metabolism, depending on the various genotypes of CYP2D6 [14]. Among the 150 identi ed alleles, multiple mutations such as CYP2D6*3, CYP2D6*4, CYP2D6*5 and CYP2D6*6 are considered to contribute to compromised CYP2D6 enzyme activity [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its CDS is 1338~1491bp in length and encodes 446 497 amino acids. The heterogeneity of CYP2D6 monooxygenase activity varies from complete dysfunction to ultra-rapid enzyme metabolism, depending on the various genotypes of CYP2D6 [14]. Among the 150 identi ed alleles, multiple mutations such as CYP2D6*3, CYP2D6*4, CYP2D6*5 and CYP2D6*6 are considered to contribute to compromised CYP2D6 enzyme activity [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the heterogeneity of CYP2D6 activity is predominantly governed by its genetic variation [13], and that decreased CYP2D6 isoenzyme activity caused by genetic polymorphisms would obstruct the generation of 5-hydroxy-primaquine, making large doses or repeated use of primaquine necessary to compensate for the declined e cacy of primaquine. Meanwhile, primaquine can cause life threatening hemolysis in patients with Glucose-6-Phosphate Dehydrogenase (G6PD) de ciency, subsequently in icting dual hazards, including low e cacy of anti-relapse and acute hemolysis, on the patients [9,[14][15]. So the patient's G6PD gene type should be identi ed by care workers prior to receiving anti-relapse treatment of vivax malaria and based on our and others' ndings, it should be considered to test for CYP2D6 genotype and predicted enzyme activity as well [14,[16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not yet know the extent of this problem with regard to the frequencies of CYP2D6 alleles associated with PQ therapeutic failure, but the significantly impaired CYP2D6 *10 allele (a particular genetic variant of CYP2D6 gene) is relatively common among Southeast Asians, at about 35% frequency [44]. It may be that many Asians will be unable to adequately metabolize PQ and achieve successful radical cure [45].…”
Section: Latent and Sub-patent P Vivaxmentioning
confidence: 99%
“…Studies have found that the heterogeneity of CYP2D6 activity is predominantly governed by its genetic variation [13], and that decreased CYP2D6 isoenzyme activity caused by genetic polymorphisms would obstruct the generation of 5-hydroxy-primaquine, making large doses or repeated use of primaquine necessary to compensate for the declined e cacy of primaquine. Meanwhile, primaquine can cause life threatening hemolysis in patients with Glucose-6-Phosphate Dehydrogenase (G6PD) de ciency, subsequently in icting dual hazards, including low e cacy of anti-relapse and acute hemolysis, on the patients [9,[14][15]. So the patient's G6PD genotype should be identi ed by care workers prior to receiving anti-relapse treatment of vivax malaria and based on our and others' ndings, it should be considered to test for CYP2D6 genotype and predicted enzyme activity as well [14,[16][17].…”
Section: Introductionmentioning
confidence: 99%